A Social/Behavioral Program for the Adolescent Student with Serious Learning Problems. - Meisgeier, Charles (Focus on Exceptional Children, 1981)
The article discusses the need for a social/behavioral program for adolescent students with serious learning problems. Studies show that failure to develop critical competencies in the microcosmic culture of the elementary classroom can confirm a child's fear of insignificance and powerlessness. The program is designed to address the problem by promoting a strong self-image and increasing acceptance and communication with peers, teachers, and others. It influences academic achievement and overall success orientation by providing detailed instruction in broad areas and by exposing students to a series of structured success experiences.